Implikasi Hukum Pembayaran Royalti terhadap Hak Eksklusif Pencipta Lagu di Indonesia - Dinda Wulandari (Jurnal Hukum Lex Generalis, 2026)
Copyright on songs and/or music is a form of intellectual property protected by law to guarantee the economic rights of the creator. In practice, the use of songs in commercial performances is still frequently carried out without the creator's permission, under the assumption that royalty payments through collective management organizations are sufficient to fulfill legal obligations. The problem examined in this research is: what are the legal implications of using artistic works in commercial performances without the creator's permission? This research employs a normative legal research method with a statutory approach and a conceptual approach. The results indicate that the creator's permission is the primary requirement for the commercial use of a song, while royalty payment is a consequence of authorized use. Government Regulation Number 56 of 2021 regulates the mechanism for collective royalty management, but it does not abolish the creator's exclusive right to grant permission. Therefore, the use of songs without the creator's permission still entails legal liability for the user and legal protection for creators must be consistently enforced to create legal certainty within the music industry.